Joint Meeting of the Specialized Russian Federation Ministry of Health Commission on the Gastroenterology Specialty and the Chief Gastroenterologists of the Russian Federal Subjects - A. A. Sheptulin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
.